Latin American Literature at the Millennium : Local Lives, Global Spaces - Raynor, Cecily; Raynor, Cecily (Book collections on Project MUSE., 2021)
"Latin American Literature at the Millennium: Local Lives, Global Spaces analyzes literary constructions of locality from the early 1990s to the mid-2010s. In this astute study, Raynor reads work by Luiz Ruffato, Wilson Bueno, Roberto Bolaño, João Gilberto Noll, and Bernardo Carvalho to reveal representations of the human experience that unsettle conventionally understood links between locality and geographical place. The book raises vital considerations for understanding the region's transition into the twenty-first century, and for evaluating Latin American authors' representations of everyday place and modes of belonging. It examines relevant theory on globalization and historical context, including a discussion of the political and economic forces at work when considering Latin America's engagement with global processes. Across its chapters, it traces localizing techniques in canonical works as well as under-studied and peripheral texts, exploring "local" as a plural concept constructed through language, memory, and patterned affective attachments. Students and scholars of Hispanic and Lusophone studies will find it to be a critical text"